The Effect of Nigella sativa Oil to Prevent Decubitus among Bedrest Patients - Mardhiah (Talenta Publisher, 2021)
Using Nigella sativa oil for skin care is a nursing measure to maintain skin integrity to prevent further tissue damage. The oil contains thymoquinone (27.8%-57%), which has been tested to heal a wound, acting as a potent analgesic and anti-inflammatory. Linoleic acid (57.9%) and linolenic acid (0.2%) act as cell-forming substances and helping to moisturize the skin. This study aims to discover the effect of Nigella sativa oil, which is applied to prolonged bedridden patients with the risk of decubitus. This study used a quasi-experimental design with one group pretest-posttest design. Random sampling was used to acquire 34 people as samples by using the probability sampling technique. This study also used paired sample test as a research analysis. The result showed a significant effect using Nigella sativa oil for skin care with a p-value = 0.000 (p<0.05).